1995
DOI: 10.1007/s001250050341
|View full text |Cite
|
Sign up to set email alerts
|

Serological evaluation of the role of cytomegalovirus in the pathogenesis of IDDM: a prospective study

Abstract: SummaryTo study the possible temporal association between primary cytomegalovirus infection and the appearance of islet cell autoantibodies or the development of insulin-dependent diabetes mellitus (IDDM) cytomegalovirus antibodies were analysed from follow-up sera of 46 initially non-diabetic siblings of diabetic children who either manifested clinical IDDM (22 siblings) or turned islet cell antibody positive (24 siblings) during the prospective observation (mean follow-up time 2.9 years). Secondly, cytomegal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
2

Year Published

1998
1998
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 10 publications
0
13
2
Order By: Relevance
“…Beside several case reports of recent‐onset IDDM with a preceding or concurrent Coxsackie B infection,33 epidemiological studies34 have shown a high frequency of IgM antibodies against Coxsackie B in children newly diagnosed with IDDM 32,35. There are, however, also contradictory results, since some reports have been unable to find any differences in antibody prevalence and titer against Coxsackie virus36 or even decreased levels of antibodies 37.…”
Section: Enterovirus/coxsackie B Virusmentioning
confidence: 99%
See 1 more Smart Citation
“…Beside several case reports of recent‐onset IDDM with a preceding or concurrent Coxsackie B infection,33 epidemiological studies34 have shown a high frequency of IgM antibodies against Coxsackie B in children newly diagnosed with IDDM 32,35. There are, however, also contradictory results, since some reports have been unable to find any differences in antibody prevalence and titer against Coxsackie virus36 or even decreased levels of antibodies 37.…”
Section: Enterovirus/coxsackie B Virusmentioning
confidence: 99%
“…Single‐case reports of IDDM after cytomegalovirus (CMV) infection have been reported in children68 and adults 69‐71. More indirect evidence came from studies showing that 35% of newly diagnosed IDDM patients showed serological evidence of recent CMV infection and association with islet cell autoantibodies 70,72‐74. On the other hand a prospective study from Sweden screening 16,474 newborns for congenital CMV infection was unable to detect any correlation of CMV infection with diabetes 75.…”
Section: Cytomegalovirusmentioning
confidence: 99%
“…Ten publications were included—1 letter and 9 articles (Figure ). Of these, 6 were nested case‐control studies using samples collected as part of prospective birth cohorts . One study contained 2 case groups with substantial patient overlap; the case group with more detailed virus detection data was included in meta‐analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Three studies utilised radioimmunoassay (RIA) and 9 employed enzyme linked immunosorbent assay (ELISA) for virus detection . One study tested IgG avidity for CMV and another used plaque neutralisation assay (PNA) for EV . Five additionally performed nucleic acid testing to detect EV RNA .…”
Section: Resultsmentioning
confidence: 99%
“…In addition to EVs, several other viruses have been analyzed in the DIPP cohort including adeno‐, influenza A , respiratory syncytial, rota‐, noro‐, parecho‐ and rhinoviruses ( , , and unpublished observations). Our previous studies in other Finnish cohorts screened also adeno‐, mumps, cytomegalo‐, Epstein‐Barr, and parainfluenzaviruses . None of these viruses have shown similar risk association with T1D as EVs.…”
Section: How Dipp Study Has Contributed To the Progress In This Fieldmentioning
confidence: 99%